Du « gothique picard » au « picard renaissant » : les voûtes de la chapelle du Saint-Esprit de Rue (1500-1525) - Labrecque, Claire (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 1996)
Although the Chapel of Saint-Esprit at Rue (Picardy) has, until now, been considered as one of the finest examples of Flamboyant architecture in its maturity, it is argued here that the building actually has a hybrid character. Moreover, its hybrid character is probably the reason why so many authors have previously experienced difficulties in classifying the vaults. The author is convinced that the Chapel of Saint-Esprit was one of the first building sites in northern France to experiment with the integration of Renaissance components in Gothic structures. The vaults, in particular, are analysed in order better to understand the process of transformation from Flamboyant to Renaissance style. Despite the use of Renaissance components in the vaults of the chapel, a resistance to Italian novelties is discernable, at the same time, in the continuation of local and vernacular practices.